Dynamiques inclusives, vecteurs de régularisation du droit à l’éducation scolaire des enfants au centre du Mali : des éléments de repère. (International Journal of Scientific Research and Management (IJSRM), 2024)
Since 2012, insecurity and violence fueled by multiple vulnerabilities have rapidly spread to Mali and other Sahel countries, leading to an unprecedented humanitarian crisis in these countries (Jean Claude Ndabananiye, 2021). These security crises have affected the education sector in particular. This article formulates options for regularizing the right to school education for children in central Mali. We adopted a mixed methodology (quantitative and qualitative). At the end of data collection we had the following results. In Ténenkou 93.6% of teachers find that educational establishments destroyed by armed or jihadist groups must be rehabilitated. In the Mopti district 54.7% of heads of household affirm that NGOs have provided support with school kits to students. In the Bankass circle, 76.9% of teachers believe that setting up a support course program would be an optimal solution to remedy the difficulties children face. In Douentza, 78.7% of respondents think that the establishment of a mixed program (classical and Koranic school) would be an optimal solution for regularizing schools in central Mali.